Reconstructing warm inflation - Ramón Herrera (European Physical Journal C: Particles and Fields, 2018)
Abstract The reconstruction of a warm inflationary universe model from the scalar spectral index $$n_S(N)$$ nS(N) and the tensor to scalar ratio r(N) as a function of the number of e-folds N is studied. Under a general formalism we find the effective potential and the dissipative coefficient in terms of the cosmological parameters $$n_S$$ nS and r considering the weak and strong dissipative stages under the slow roll approximation. As a specific example, we study the attractors for the index $$n_S$$ nS given by $$n_{S}-1\propto N^{-1}$$ nS-1∝N-1 and for the ratio $$r\propto N^{-2}$$ r∝N-2 , in order to reconstruct the model of warm inflation. Here, expressions for the effective potential $$V(φ )$$ V(ϕ) and the dissipation coefficient $$Γ (φ )$$ Γ(ϕ) are obtained.